PROGRESS AND PROSPECTS IN THERAPEUTICS AGAINST HIV INFECTION (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Tremendous advances have occurred in recent decades in the development of safe and effective medications for the treatment of viral diseases. Currently there are more than 20 HIV drugs approved for use in humans. Combined chemotherapy has been found useful for a number of viral infections comprising drugs with different mechanism of action. HIV treatment guidelines recommend the use of two nucleoside reverse transcriptase inhibitors (NsRTIs) plus a third antiretroviral drug for treatment-naive patients with AIDS that include non-nucleoside reverse transcriptase inhibitors (NNRTIs; eg, efavirenz), ritonavir-boosted protease inhibitors (eg, darunavir, atazanavir), and integrase inhibitors (eg, raltegravir, dolutegravir). However emergence of drug resistant HIV variants and their dissemination impede proper treatment of AIDS. Preferred regimens as first-line treatment in patients with suboptimum adherence comprise drugs with improved potency, safety and infrequent selection for resistance-associated mutations. The present review stands for an update on facts and phenomena of present, past, and future use of antiretrovirals based upon the available documents in SCI and non-SCI journals.